Qur’anic Pedagogical Ethics: An Exegetical Study of the Etiquette of Teaching the Qur’an - Azzahra, Rufaidah (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2025)
The decline in ethical standards among leaders, teachers, and students in the field of education has the potential to undermine the quality of education. A number of teachers, who should serve as role models, have instead engaged in misconduct, such as violence, sexual harassment, and a lack of professional commitment. This phenomenon tarnishes the reputation of both individuals and the teaching profession as a whole. This study aims to explore the Qur’anic guidance regarding the ethics and conduct of Qur’an instructors by referring to exegetical works. The method used is qualitative, specifically a literature review. Employing an analysis based on thematic exegesis, this article seeks to uncover the concepts of ethics and conduct for instructors as presented in exegetical texts. The results of the study indicate that QS. Hud [11]: 15–16 and Asy-Syura [42]: 20 emphasize the importance of maintaining sincere intentions; QS. al-Maidah [5]: 8 emphasizes justice and objectivity in education; QS. al-Ahzab [33]: 21 presents the Prophet Muhammad, peace be upon him, as the primary role model for educators, and QS. al-Nahl [16]: 125 teaches the importance of wisdom and gentleness in offering advice. This study contributes to enriching the understanding of thematic exegesis regarding the ethics and conduct of Qur’an teachers while providing practical guidelines for educators to apply Qur’anic values in modern education.